Rodent management in arid regions - Tripathi, R. S.; Chaudhary, Vipin (Indian Farming, 2018)
Rodents are serious pest of agriculture, causing 2 to 15% losses to crops at pre-harvest stage and up to 5% losses in storage. In hot arid regions, only 7 to 8 species may be considered as pests which cause immense losses to the crops, fodder grasses and forestry plantations in arid regions. Besides non-chemical control like trapping, sanitation, physical exclusion of rodents, chemical control through rodenticide is cheapest and the most feasible. Application of 2 to 2.5% zinc phosphide in cereal bait is recommended for rodent management in fields. It should be followed by bromodiolone (0.005%) baiting for managing residual rodent populations surviving after zinc phosphide baiting. For indoor condition only bromodiolone (0.005%) bait is recommended.